STUDI KASUS PROSEDUR PEMERIKSAAN RADIOGRAFI THORAX PADA KASUS DENGUE HAEMORAGIC FEVER (DHF) DI INSTALASI RADIOLOGI RS ROEMANI MUHAMMADIYAH SEMARANG - Umi Uswatun Khasana,; Ayu Mahanani,; Taufiq Facruddin Zen, (Journal of Innovation Research and Knowledge, 2025)
Introduction: Dengue Hemorrhagic Fever (DHF) is a dengue fever disease that can be fatal if not treated quickly and appropriately. Generally, the supporting actions taken are thorax examinations to see if there is fluid in the pleura. Thorax examinations in pleural effusion cases are performed using AP, PA and Lateral Dicubitus projections with a 5-minute patient tilt preparation. While at Roemani Hospital, Semarang, thorax examinations in DHF cases use AP and RLD (PA) projections with a 30-minute tilt preparation. The purpose of this study was to determine the thorax examination procedure for DHF cases at the Radiology Installation of Roemani Hospital, Semarang, and to determine the reasons for the RLD projection using a 30-minute waiting time. Methods: This study uses qualitative research with a case study approach conducted at Roemani Muhammadiyah Hospital, Semarang in December 2024-May 2025. The data collection methods used were observation, documentation and interviews with radiographers and radiologists. Data analysis was obtained from data collection at Roemani Hospital Semarang, after which the data was reduced to take the important things and then presented in the form of scientific papers and conclusions were drawn. Results: The results of the study showed that in the examination of the thorax of DHF cases in the RLD projection using waiting time, the reason is so that the fluid is maximally collected below and in the examination of the thorax using AP and RLD (PA) projections the reason for using the RLD projection in the PA position is to minimize fixation tools and because of the equipment factor at Roemai Hospital Semarang. Conclusion: The procedure for examining the thorax of DHF cases at the Radiology Installation of Roemani Hospital Semarang was carried out with AP and RLD (PA) projections. Patient preparation was carried out with a waiting time of 30 minutes the reason for the 30-minute waiting time on the RLD projection is so that the fluid is maximally collected below and in the RLD projection using the PA position is to make it easier for the patient and minimize fixation tools and equipment factors